The ram cichlid (Mikrogeophagus ramirezi) learns an associative task: a new fish species for memory research - Benjamin Tsang; Veronica Venditti; Celina Micaela Javier; Robert Gerlai (Scientific Reports, 2023)
Abstract Fish are the most species rich and evolutionarily oldest vertebrate taxon. This represents opportunities for biologists who intend to employ laboratory animals in their comparative or translational research. Yet, the overwhelming majority of such studies use a single fish species, the zebrafish, a suboptimal strategy from the comparative standpoint. Neuronal plasticity (learning and memory) is perhaps one of the most complex biological phenomena from a mechanistic standpoint, and thus its analysis could benefit from the use of evolutionarily ancient and simple vertebrate model organisms, i.e., fish species. However, learning & memory research with the zebrafish has been replete with problems. Here, we employ a novel fish species, the ram cichlid, we argue will be particularly appropriate for this purpose for practical as well as ethological/ecological reasons. First, we investigate whether the ram cichlid exhibits innate preference for certain colours (red, blue, yellow or green) in a four-choice task, the plus maze. Subsequently, we pair the apparently least preferred colour (green, the conditioned stimulus or CS) with food reward (the unconditioned stimulus, US) in the plus maze, a CS–US associative learning task. After eight pairing trials, we run a probe trial during which only the CS is presented. At this trial, we find significant preference to the CS, i.e., acquisition of memory of CS–US association. We argue that our proof-of-concept study demonstrating fast acquisition of CS–US association in the ram cichlid, coupled with the universal utility of some genome editing methods, will facilitate the mechanistic analysis of learning and memory.